Hypertension as Risk Factor in Diabetic Retinopathy in type-2 Diabetes - Saeed Iqbal, Manzoor A Mirza, Tahir Masaud Arbab, Sajjad Hanif (Pakistan Journal of Ophthalmology, 2008)
Purpose: To evaluate hypertension as a risk factor for diabetic retinopathy in type 2 diabetic patients. Material and Methods: This case control study of 100 patients, using nonprobability purposive sampling, between 40-70 years of ages with equal sex distribution was conducted in the medical department of Sir Syed hospital, Karachi, from August 2007 to October 2007. . All patients were screened for diabetic retinopathy. The patients with diabetic retinopathy were placed in group DR (diabetic retinopathy) and patients without retinopathy were placed in group NDR (non-diabetic Retinopathy). Blood pressure measurements were done in all these patients along with fasting blood sugar, random blood sugar and Hb1c. The data was analyzed on SPSS for windows. The comparison of two groups i.e., case control was done by student t-test. Correlation of hypertension to proliferative retinopathy was evaluated by odd ratio. Results: The correlation between diabetic retinopathy was analyzed in 100 patients. Systolic and diastolic blood pressures were significantly higher in patients with retinopathy (Mean systolic 136 ± 16 mmHg and mean diastolic 84 ± 10 mmHg) than those without retinopathy (Mean systolic 129 ± 17 mmHg and mean diastolic 78 ± 12 mmHg). There was significant correlation of diabetes retinopathy with systolic hypertension (P <0.02) and diastolic hypertension (P <0.007) Conclusion. The study results suggest that there is strong association between diabetic retinopathy and hypertension.